Production of thermoplastic matrix pre-impregnated materials to manufacture composite pultruded profiles - Tinoco, V. (2013)
The aim of the work was optimizing the continuous production of new continuous carbon fibers reinforced polypropylene matrix pre-impregnated materials (towpregs). This raw-material, produced by dry deposition of polypropylene (PP) powder in an equipment built by the Institute for Polymers and Composites (IPC), was used to manufacture composite pultruded profiles in a recently developed prototype equipment assembled in the Engineering School of the Polytechnic Institute of Porto (ISEP).